2022
DOI: 10.3847/1538-4357/ac69d9
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Analysis of KIC 1573174: Shedding Light on the Nature of HADS Stars

Abstract: We propose that KIC 1573174 is a quadruple-mode δ Scuti star with pulsation amplitudes between those of the high-amplitude Delta Scuti star group and average low-amplitude pulsators. The radial modes detected in this star provide a unique opportunity to exploit asteroseismic techniques up to their limits. Detailed frequency analysis is given for the light curve from the Kepler mission. The variation of the light curve is dominated by the strongest mode with a frequency of F0 = 7.3975 day−1, as shown by Fourier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Then a sensible method to model TIC 448892817 is by using Petersen diagrams. Petersen diagrams, therefore, provides a useful diagnostic method in terms of constraining these parameters of radial pulsators (e.g., Petersen 1973;Petersen & Christensen-Dalsgaard 1996;Daszyńska-Daszkiewicz et al 2020;Bowman et al 2021;Lv et al 2022). We provide the best-fitting mass, Z, effective temperature, luminosity, surface gravity, age, theoretical frequency of fundamental, first overtone radial modes, and their ratios listed in Table 4.…”
Section: Stellar Model and Fitting Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then a sensible method to model TIC 448892817 is by using Petersen diagrams. Petersen diagrams, therefore, provides a useful diagnostic method in terms of constraining these parameters of radial pulsators (e.g., Petersen 1973;Petersen & Christensen-Dalsgaard 1996;Daszyńska-Daszkiewicz et al 2020;Bowman et al 2021;Lv et al 2022). We provide the best-fitting mass, Z, effective temperature, luminosity, surface gravity, age, theoretical frequency of fundamental, first overtone radial modes, and their ratios listed in Table 4.…”
Section: Stellar Model and Fitting Resultsmentioning
confidence: 99%
“…Advances in sophisticated data processing techniques, such as Lares-Martiz et al (2020), have made possible that frequencies of low amplitude could be found in the spectrum of HADS as well (e.g., Poretti et al 2011;Bowman et al 2021). According to the ratio among the frequencies, the radial modes of HADS could be identified (Petersen 1973), and then by constructing radial frequencies models and comparing the models ratio with the observed ratio, several basic parameters of the star could be obtained, as well as the evolutionary stage (e.g., Xue et al 2018;Bowman et al 2021;Daszyńska-Daszkiewicz et al 2022;Lv et al 2022). A detailed seismic modeling of SX Phe performed by Daszyńska-Daszkiewicz et al (2020), confirmed its post-main-sequence evolutionary stage by using a high-precision photometry collected from TESS mission.…”
Section: Introductionmentioning
confidence: 99%
“…The smaller Galactic Scuti amplitudes, caused by smaller temperature fluctuations lead to a flatter PC relation at maximum light. Hence, we have good support for the HIF stellar photosphere theory as described in Simon et al 1993;Das et al 2020, and references therein. We also note that there is some controversy over the pulsation mode of Scuti stars and in fact whether they may be pulsating in a number of modes and/or have a non-radial component (Netzel et al 2022;Lv et al 2022;Khruslov 2022;Netzel & Smolec 2022). When we cross-checked our sample with the triple mode stars as listed in Netzel et al (2022), we found 32 such stars in our sample.…”
Section: A Possible Theoretical Explanationmentioning
confidence: 90%
“…A careful examination was performed to select and discard the combination frequencies f c = M f i + L f j , where M and L are integers. In general, the combination frequencies f c have amplitudes much lower than the parent (or independent) frequencies f i and f j (Breger & Lenz 2008;Breger et al 2011;Lv et al 2022), which are more severe in higher-order terms. Pápics (2012) recommended that one should try to find higher-order combinations only when the presence of second-order terms is proven.…”
Section: Identification Of Independent Frequenciesmentioning
confidence: 98%